Elevated CD8 T-cell counts and virological failure in HIV-infected patients after combination antiretroviral therapy - Ku, Nam Su (Medicine (Baltimore), 2016)
Elevated CD8 counts with combination antiretroviral therapy (cART) initiation may be an early warning indicator for future treatment failure. Thus, we investigated whether elevated CD8 counts were associated with virological failure (VF) in the first 4 years of cART in Asian HIV-infected patients in a multicenter regional cohort. We included patients from the TREAT Asia HIV Observational Database (TAHOD). Patients were included in the analysis if they started cART between 1996 and 2013 with at least one CD8 measurement within 6 months prior to cART initiation and at least one CD8 and viral load (VL) measurement beyond 6 months after starting cART. We defined VF as VL ≥400 copies/mL after 6 months on cART. Elevated CD8 was defined as CD8 ≥1200 cells/μL. Time to VF was modeled using Cox regression analysis, stratified by site. In total, 2475 patients from 19 sites were included in this analysis, of whom 665 (27%) experienced VF in the first 4 years of cART. The overall rate of VF was 12.95 per 100 person-years. In the multivariate model, the most recent elevated CD8 was significantly associated with a greater hazard of VF (HR = 1.35, 95% CI 1.14–1.61; P = 0.001). However, the sensitivity analysis showed that time-lagged CD8 measured at least 6 months prior to our virological endpoint was not statistically significant (P = 0.420). This study indicates that the relationship between the most recent CD8 count and VF was possibly due to the CD8 cells reacting to the increase in VL rather than causing the VL increase itself. However, CD8 levels may be a useful indicator for VF in HIV-infected patients after starting cART.